Identification of maximum volume in strength training. Part 2: Maximum number of sets - Desgorces, F.-D.; Testa, M. (First international symposium sciences and practices in swimming, 2006)
Our study aimed to determine the maximum number of sets in bench press according to the individual maximum number of repetitions. 5 physical education students participated to the study constituted by 16 strength training sessions over a 3-month period. During these sessions subjects completed sets till exhaustion. The maximum number of repetitions recorded determined an intermediate endurance profile of the subjects compared to the "strongs" (power-lifting) and the "resistants" (swimmers-rowers). There was no difference in the number of sets performed between individuals. Thus, in accordance with previously results on running, when the capacity to repeate lift was used the set number did not change. The graphical model proposed could allowed to better individualized training sessions according to the goal and to the fatigue-induce aimed.